Penerapan Media Pohon Literasi Untuk Meningkatkan Minat Baca Siswa Sekolah Dasar - Irwan, Irwan; Sumantri, Sri; Ridwan, Muhamad; Faslia, Faslia; Manan, Manan; Gawise, Gawise; Lusmawati , Lusmawati; Citra, Devi (Universitas Pahlawan Tuanku Tambusai, 2025)
This activity discusses the application of literacy tree media as an innovation strategy in increasing students’ interest in reading at SD Negeri 2 Baubau. The literacy tree is a creative approach that integrates visual elements to increase students’ interest in reading, considering the importance of literacy in developing individual potential and society as a whole. The problem faced is the decline in students’ interest in reading due to a lack of interest and stimulation in learning. The method used in this service involves the desig and implementation of literacy trees in school. The results of service and proctical experience sho that the application of literacy tree media at SD Negeri 2 Baubau is effective in creating a lerning environment that support students’ literacy development. Thus, this activity provides guidance for educators to apply literacy tree media as an effective strategy in increasing students’ interest in reading.